Acupuncture for post-cesarean pain and gastrointestinal function recovery: a meta-analysis and systematic review - Liu, Hejing; Xing, Kehan; Liao, Cai; Wang, Jiapei; Tang, Chenglin; Huang, Siqin (Frontiers in Medicine, 2025)
ObjectivePostoperative pain and gastrointestinal dysfunction are common complications after cesarean section, significantly affecting maternal recovery and quality of life. Acupuncture has recently shown promise in alleviating postoperative pain and promoting the recovery of gastrointestinal function. This study aimed to assess the effectiveness of acupuncture in relieving postoperative pain and improving gastrointestinal function after cesarean section via a meta-analysis.Materials and methodsA comprehensive search for randomized controlled trials (RCTs) examining acupuncture for post-cesarean pain and gastrointestinal function was conducted across multiple databases, covering literature up to 1 February 2025. Data analysis was conducted using Stata 15.ResultA total of 26 studies involving 2,641 patients were included. This meta-analysis evaluated the effects of acupuncture on postoperative pain, bowel sound recovery, and time to first flatus. The results demonstrated that acupuncture significantly reduced VAS at 6 h (SMD = −0.36, 95%CI [−0.65, −0.07]), 12 h (SMD = −1.23, 95%CI [−1.81, −0.64]), 24 h (SMD = −1.06, 95%CI [−1.56, −0.56]), and 48 h (SMD = −0.96, 95%CI [−1.76, −0.17]). Additionally, acupuncture significantly shortened bowel sound recovery time (SMD = −2.26, 95% CI [−2.97, −1.54]) and anal exhaust time (SMD = −2.41, 95% CI [−3.21, −1.61]). Subgroup analysis revealed that conventional acupuncture was effective across the majority of outcomes, while electroacupuncture showed comparatively weaker effects at certain time points. However, the presence of substantial heterogeneity (I2 values above 90%), along with variations in study quality and acupuncture protocols, could limit the accuracy and generalizability of the findings.ConclusionThis meta-analysis suggests that acupuncture may effectively relieve pain and improve gastrointestinal function after cesarean section. The study’s results showed significant improvements in pain scores and gastrointestinal recovery indicators, including bowel sound recovery time and anal exhaust time. However, the results should be interpreted with caution due to the high degree of heterogeneity and variability in study quality and acupuncture protocols. Further high-quality, large-scale RCTs are needed to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025638696.